2020
DOI: 10.36076/ppj.2020/23/e219
|View full text |Cite
|
Sign up to set email alerts
|

Early Treatment with Temporary Spinal Cord Stimulation Effectively Prevents Development of Postherpetic Neuralgia

Abstract: Background: Some 7.7% of the Chinese population suffer from herpes zoster each year, with 29.8% proceeding on to develop postherpetic neuralgia (PHN). This amounts to over 32 million people per year. PHN is preceded by 2 phases of pain: acute herpetic neuralgia (AHN), and subacute herpetic neuralgia (SHN). Considering the large individual and economic burden, preventing the transition of AHN/SHN to PHN is crucial. However, to date this has been difficult. Objectives: To evaluate the efficacy of temporary spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The author reported that the change in NRS was greater for tSCS than for interventional procedures, indicating that tSCS improves pain in response to ZAP resistance to interventional therapy. In an observational study by Huang et al, tSCS was also performed in 99 patients with ZAP who had failed pharmacological and interventional therapy [ 16 ]. They reported that performing tSCS in ZAP within 80 days of onset prevented postherpetic neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…The author reported that the change in NRS was greater for tSCS than for interventional procedures, indicating that tSCS improves pain in response to ZAP resistance to interventional therapy. In an observational study by Huang et al, tSCS was also performed in 99 patients with ZAP who had failed pharmacological and interventional therapy [ 16 ]. They reported that performing tSCS in ZAP within 80 days of onset prevented postherpetic neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation, usually spinal cord stimulation (SCS), is a convenient, reversible, purely physical, minimally invasive treatment method, and without the implantation of a pulse generator, it is less invasive, more effective, and safer. It has been widely used in the treatment of herpes zoster neuralgia 2,4 , and has now become an important minimally invasive neuromodulation technique for the treatment of herpes zoster-related neuralgia in China.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Post-herpetic trigeminal neuralgia is a neuropathic pain caused by varicella-zoster virus (VZV) infection of the trigeminal ganglion or branches, which remains or reappears after herpes crusting 1 .In terms of treatment with drugs, such as antineuralgia, tricyclics, and weak opioids, patients often have difficulty accepting drug side effects or adverse reactions [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest rate was 30.5 per 1,000 personyears among the patients aged ≥ 80 years (4). Postherpetic neuralgia is a painful complication affecting to 30% of patients with HZ (5). Postherpetic neuralgia may occur after recovery from the acute stage, and can last from months to years.…”
Section: Introductionmentioning
confidence: 99%